2021
DOI: 10.1097/ogx.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

Physical Examination—Indicated Cerclage in Twin Pregnancy: A Randomized Controlled Trial

Abstract: Twin pregnancies in the United States represent a small proportion of births each year, but they are associated with increased risks of preterm birth (PTB), low birthweight, and perinatal mortality. In the setting of cervical dilation in the second trimester, the risks for complications in a twin pregnancy are even higher. In singleton pregnancies, physical examinationindicated cerclage has been shown to decrease PTB and loss of pregnancy. However, the data for this procedure in twin pregnancies are limited. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…Effective PTB prevention measures in multiple gestations, in general, and, more specifically, in monochorionic diamniotic twin pregnancies complicated with TTTS undergoing FLS, have not yet been defined. In multiple gestation with a normal or short cervix, interventions such as other forms of tocolytics, cerclage, progesterone, pessary, routine hospitalisation, or bed rest have not been proven to prolong pregnancy or improve neonatal morbidity and mortality 10,28–40 . In the setting of TTTS treated with FLS with short preoperative CL, cervical cerclage did not prolong pregnancy in a retrospective, multicentre cohort study 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective PTB prevention measures in multiple gestations, in general, and, more specifically, in monochorionic diamniotic twin pregnancies complicated with TTTS undergoing FLS, have not yet been defined. In multiple gestation with a normal or short cervix, interventions such as other forms of tocolytics, cerclage, progesterone, pessary, routine hospitalisation, or bed rest have not been proven to prolong pregnancy or improve neonatal morbidity and mortality 10,28–40 . In the setting of TTTS treated with FLS with short preoperative CL, cervical cerclage did not prolong pregnancy in a retrospective, multicentre cohort study 41 .…”
Section: Discussionmentioning
confidence: 99%
“…In multiple gestation with a normal or short cervix, interventions such as other forms of tocolytics, cerclage, progesterone, pessary, routine hospitalisation, or bed rest have not been proven to prolong pregnancy or improve neonatal morbidity and mortality. 10,[28][29][30][31][32][33][34][35][36][37][38][39][40] In the setting of TTTS treated with FLS with short preoperative CL, cervical cerclage did not prolong pregnancy in a retrospective, multicentre cohort study. 41 Our study showed that LIT use significantly increased the FLS-to-delivery interval regardless of the length of the cervix and gestational age of the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When we interpret study results on approaches to cerclage for cervical insufficiency (beyond cerclage vs. no-cerclage), wide variation exists in most study interventions for management, including surgical approach (eg, McDonald vs. Shirodkar cerclage, suture type) and adjunct interventions (eg, antibiotics, tocolytics, amniocentesis, bed rest) 59. Roman et al60 performed a multicenter RCT and found that use of a physical examination-indicated cerclage reduced the rate of spontaneous preterm birth for twin pregnancies with asymptomatic cervical dilation before 24 weeks when compared with no cerclage (relative risk: 0.7, 95% confidence interval: 0.46-0.96). However, 82% of those in the cerclage intervention arm also received tocolytic and antibiotics periprocedure.…”
Section: Other Study Considerationsmentioning
confidence: 99%
“…16 There is, however, now high-quality evidence supporting the use of physician examination indicated cerclage in twin pregnancies. 17,18 Areas for further investigation include the use of progesterone in twin pregnancies with a short cervix, the role of the microbiome and inflammation in preterm birth in multiple pregnancy. 19 A key knowledge gap highlighted in the recent MBRRACE Special Report on perinatal mortality in twins is the best management of delivery of the second twin in a diamniotic pregnancy where the first twin has delivered spontaneously at an extremely preterm gestation and the second sac remains intact and there is no spontaneous labour or maternal compromise.…”
Section: Preterm Birthmentioning
confidence: 99%
“…There is no benefit with the Arabin pessary 15 in the management of twin pregnancies with a short (<35 mm) cervix, or in the use of vaginal progesterone in unselected twin pregnancies 16 . There is, however, now high‐quality evidence supporting the use of physician examination indicated cerclage in twin pregnancies 17,18 . Areas for further investigation include the use of progesterone in twin pregnancies with a short cervix, the role of the microbiome and inflammation in preterm birth in multiple pregnancy 19 .…”
Section: Preterm Birthmentioning
confidence: 99%